Cultural Resilience of Livestock Production in South West Sumba - Wilhelmus Yape Kii; Akhmad Sodiq; Juni Sumarmono; Novie Andri Setianto; Zainal Aznam Bin Mohd Jelan; Agus Susanto; Muhamad Bata; Agustinah Setyaningrum; Gede Suarta (ANIMAL PRODUCTION, 2026)
The sustainability of livestock production systems is influenced by environmental, economic, and social conditions, as well as technological advancements. In Sumba, Indonesia, livestock is not only an economic asset but also a symbol of social status, integral to various traditional rituals. This study aimed to identify local livestock production systems and examine the role of culture in their sustainability across three agroecosystem zones: Kodi, Wewewa, and Loura. The research employed a structured survey methodology based on the Livestock On-Farm Trials method and involving 420 farmers. Results show that Sumba's livestock production systems apply an integrated crop- agro-pastoral, kaliwo agroforestry-livestock system, also rangeland-based, predominating in Loura. Socio-cultural aspects strongly influence livestock practices, with sources of capital stemming from agricultural revenues (dry-land and rice fields), kaliwo agroforestry, family inheritance, livestock barter, profit-sharing arrangements, and surplus animals from wedding dowries and other cultural ritual ceremonies. Feed resources are primarily derived from cultivated dry-land and kaliwo agroforestry. Livestock are primarily raised for cultural, ceremonial, and ritual purposes, including funerals, wedding dowries, and the pasola festival, as well as for income and education support. Preservation of local wisdom and socio-cultural values is crucial to advancing sustainable livestock production in Southwest Sumba.